Intercultural dialogue on societal nature relations: How political ecology from China inspires the search for new practices of transformation - Buschmann, Daniel (Momentum Quarterly, 2023)
In the German-speaking discourse on socio-ecological transformation, the theory of societal nature relations has gained momentum as a problem diagnosis of multiple socio-ecological crises in the Anthropocene – for scientists as well as for activists. The subsequent question of practical alternatives led to the demand for a democratization of societal nature relations. However, satisfying answers as to what exactly this means for the organization of a transformation, are yet lacking. In response, this paper pursues an intercultural dialogue with Daoist philosophy and discusses to what extent domination-free, or an-archic, nature relations represent a possible practice of socio ecological transformations. The paper concludes that transformations could be organized with action-by-non-action (wu-wei) and explores what this possibly means in theory and practice.